2021
DOI: 10.11604/pamj.2021.38.25.26755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of 646 hospitalised SARS-Cov-2 positive patients in Rivers State Nigeria: a prospective observational study

Abstract: Introduction the knowledge of epidemiologic and clinical variables in patients with SARS- CoV-2 infection provides evidence and lessons that are useful for the pandemic response, with consideration of National and sub-National variations. The objective of this study was to characterize and describe the clinical and epidemiologic features of all the hospitalised patients with COVID-19 in Rivers State Nigeria, from March to August 2020. Methods a prospective descriptive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
4
14
1
Order By: Relevance
“…A study [12] was done which shed light on how the similarity of malaria and COVID-19 symptoms may misdiagnose a malaria case as COVID-19 or vice versa or may overlook the possible co-infection. Another study on the clinical and epidemiology characteristics of 646 hospital SARS-CoV-2 positive patients in Rivers State [13] reported that age of patients with COVID-19 had been documented as a key determinant of the disease, which is in conformity with the results of this study. Therefore, from the results of the study, the prevalence of COVID-19 disease amongst returning students of University of Port Harcourt with mean aged 22 years for the males and 21years for the females is Zero (Zero prevalence), as seen after the Standard Q COVID-19 antigen test kit sample was analyzed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A study [12] was done which shed light on how the similarity of malaria and COVID-19 symptoms may misdiagnose a malaria case as COVID-19 or vice versa or may overlook the possible co-infection. Another study on the clinical and epidemiology characteristics of 646 hospital SARS-CoV-2 positive patients in Rivers State [13] reported that age of patients with COVID-19 had been documented as a key determinant of the disease, which is in conformity with the results of this study. Therefore, from the results of the study, the prevalence of COVID-19 disease amongst returning students of University of Port Harcourt with mean aged 22 years for the males and 21years for the females is Zero (Zero prevalence), as seen after the Standard Q COVID-19 antigen test kit sample was analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained in the study are also in line with the study on "Clinical and epidemiological characteristics of 646 hospitalized SARS-CoV-2 (COVID-19) positive patients in Rivers State, Nigeria" [13], reported that COVID-19 symptoms were more severe in patients aged 50 and above. This explains why this study may have obtained zero prevalence amongst returning students of the University whose age range fell within 16 and 34 for 248 study subjects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In total, 34 studies provided information on the severity of COVID-19 disease. Of them, four studies were preprints (Al Harthi et al 2020 ; Bertlich et al 2020 ; Papizadeh et al 2020 ; Patel et al 2020 ), and 30 articles were published studies (Aggarwal et al 2020 ; Alasia et al 2021 ; Alizadehsani et al 2021 ; Allenbach et al 2020 ; Amanat et al 2021 ; Borobia et al 2020 ; Delorme et al 2021 ; Elimian et al 2020 ; Ermis et al 2021 ; García-Azorín et al 2021 ; Ghaffari et al 2021 ; Goyal et al 2021 ; Izquierdo et al 2020 ; Kadiane-Oussou et al 2020 ; Kocayığıt et al 2021 ; Lechien et al 2021 ; Liotta et al 2020 ; Mao et al 2020 ; McElvaney et al 2020 ; Muñoz-Rodríguez et al 2021 ; Printza et al 2021 ; Romero-Sánchez et al 2020 ; Salepci et al 2021 ; Sobhani et al 2021 2021 ; Song et al 2021 ; Studart-Neto et al 2020 ; Sun et al 2021 ; Tomlins et al 2020 ; Vaira et al 2020 ; Vial et al 2020 ). The OD were present in 482 severely ill and 2640 non-severely ill patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Alasia et al [ 15 ] found that advanced age and presence of fever, dry cough, dyspnea, fatigue, productive cough, diarrhea, and vomiting were more associated with severe COVID-19 disease among Nigerians in Rivers State. Our cohort did not have any cases of severe COVID-19 illness requiring hospitalization during the study period, and this may be because our cohort is composed of individuals aged 40 years and under.…”
Section: Discussionmentioning
confidence: 99%